Development of a bilayered scaffold based on silk fibroin and silk fibroin/nano-calcium phosphate for osteochondral regeneration - Yan, Leping (2012)
Objectives: Osteochondral defect is a common condtion in clinic. Satisfactory outcomes are rarely achieved by traditional methods. Tissue engineering might be a promising strategy for this hinder. The aim of this study is to mimick the stratified structure of osteochondral tissue, by developing a bilayered scaffold for osteochondral regeneration. The developed bilayered scaffold is composed of a porous silk fibroin scaffold as the cartilage-like layer and a porous silk fibroin/nano-calcium phosphate (CaP) scaffold as the bone-like layer.